2017
DOI: 10.1007/s00268-017-4232-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Splenic Volume and Splenectomy on Prognosis of Hepatocellular Carcinoma Within Milan Criteria After Curative Hepatectomy

Abstract: High SV is an independent predictor of post-hepatectomy HCC recurrence and overall survival. There is no significant difference in prognosis between low SV and splenectomy groups, even though the latter had high SV. Combined splenectomy with hepatectomy for HCC and PH may improve prognosis and be an appropriate alternative when liver transplantation cannot be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Whether gastric cancer patients with DROSD have also experienced the function disorder of immunity, which lead to the patient having short- and long-term differences still requires further experimental verification. Second, it has been reported that splenic volume increase is a surrogate marker of inflammation cells accumulation and associated with worse long-term survival ( 27 , 28 ). As mentioned in the previous literature, the reduction of spleen density in acute severe pancreatitis rats was related to the increase of spleen volume ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether gastric cancer patients with DROSD have also experienced the function disorder of immunity, which lead to the patient having short- and long-term differences still requires further experimental verification. Second, it has been reported that splenic volume increase is a surrogate marker of inflammation cells accumulation and associated with worse long-term survival ( 27 , 28 ). As mentioned in the previous literature, the reduction of spleen density in acute severe pancreatitis rats was related to the increase of spleen volume ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…While hypersplenism was associated with HCC recurrence and poor outcome, splenectomy for hypersplenism improved outcomes among patients undergoing curative resection for HCC. [13,16] Similarly, using a murine orthotopic model, Li and colleagues had demonstrated that splenectomy prevented tumor growth and improved immune responses of tumor-bearing hosts by decreasing myeloidderived suppressor cells, and increasing natural killer (NK) cells and NK T cells in liver tumor tissues. [26] Similarly, Liu et al demonstrated in a murine model that splenectomy accelerated liver regeneration after partial hepatectomy of HCC by improvement of the tight junction formation which helped in establishment of hepatocyte polarity via Par 3-aPKC.…”
Section: Discussionmentioning
confidence: 99%
“…[11] In fact, high splenic volume has been independently associated with post-hepatectomy HCC recurrence and overall survival. [13] Of note, recent studies have demonstrated that hypersplenism secondary to liver cirrhosis and portal hypertension was an independent risk factor associated with HCC development. [14][15][16] The association between hypersplenism and HCC development might be multifactorial but also partially as a result of thrombocytopenia, since thrombocytopenia has also associated with an increased risk for HCC development.…”
Section: Introductionmentioning
confidence: 99%
“…BRTO increases hepatopetal portal flow and improves liver function of patients with reserve liver capacity [21]. High splenic volume is an independent predictor of the recurrence of posthepatectomy HCC and overall survival [22]. Thus, splenectomy reduces portal pressure in patients with PH and improves liver function [23].…”
Section: Discussionmentioning
confidence: 99%